Tissue specific deletion of inhibitor of kappa B kinase 2 with OX40-Cre reveals the unanticipated expression from the OX40 locus in skin epidermis. - Georgina H Cornish; Sim L Tung; Daniel Marshall; Steve Ley; Benedict P Seddon (PLoS ONE)
NF-κB signalling plays an essential role in T cell activation and generation of regulatory and memory populations in vivo. In the present study, we aimed to investigate the role of NF-κB signalling in post-activation T cells using tissue specific ablation of inhibitor of kappa-B kinase 2 expression, an important component of the inhibitor of kappa-B kinase complex in canonical NF-κB signalling. The OX40 antigen is expressed on activated T cells. Therefore, we used previously described mouse strain expressing Cre recombinase from the endogenous OX40 locus. Ablation of IKK2 expression using OX40(Cre) mice resulted in the development of an inflammatory response in the skin epidermis causing wide spread skin lesions. The inflammatory response was characterised by extensive leukocytic infiltrate in skin tissue, hyperplasia of draining lymph nodes and widespread activation in the T cell compartment. Surprisingly, disease development did not depend on T cells but was rather associated with an unanticipated expression of Cre in skin epidermis, and activation of the T cell compartment did not require Ikbk2 deletion in T cells. Employment of Cre reporter strains revealed extensive Cre activity in skin epidermis. Therefore, development of skin lesions was rather more likely explained by deletion of Ikbk2 in skin keratinocytes in OX40(Cre) mice.